Photothermal excitation in non-local semiconductor materials with variable moisture thermal conductivity according to moisture diffusivity - El-Sapa, Shreen; El-Bary, Alaa A.; Chtioui, Houda; Becheikh, Nidhal; Lotfy, Khaled (Frontiers in Materials, 2023)
In this work, a new model is described for the case of interference between thermal, plasma and elastic waves for a non-local excited semiconductor medium. The governing equations have been put under the influence of moisture diffusion in one dimension (1D) when the moisture thermal conductivity of the non-local medium is taken in a variable form. Some linear transformations were used to describe the model in the dimensionless case. The photo-thermoelasticity theory according to the moisture diffusivity was applied to describe the governing equations using Laplace transforms to obtain the analytical solutions. In the time domain, the complete solutions are obtained linearly when some of the conditions are taken and applied (thermal ramp type and non-Gaussian plasma shock) to the surface through some numerical methods of inverse Laplace transforms. Numerical simulation is used to display some physical quantities under study graphically. The current research has yielded several specific examples of great significance. Many comparisons are made under the influence of some physical variables such as relaxation times, variable thermal conductivity, non-local parameters, and reference moisture parameters through graphing and describing it theoretically.